Attainment of human wellness and preservation of ecological balance in the light of revelation: insights for policy making through Islamic principals pertaining to nature - Zainal, Mohd Farid; Ali, Mohammed Farid (IIUM Press, International Islamic University Malaysia, 2018)
The higher objectives of Shari'ah specifies five areas that needs protection and due care and they are life, religion, offspring,intellect and property. Sustainability discourse pay great attention to environmental care as well as rights of future generations and both are indeed well established in the Shari'ah. Sustainability and sustainable development emerged as disciplines that pay concerns on inter-relatedness and inter-dependent nature of environment and development (Ratna & Zainal, 2010), though some expanded the discussion to also include economic and societal aspects as well. From time to time questions were raised over the exact definition of sustainability. Clarifications were sought and somehow it might be best described as the goal of sustainable development – a state of equilibrium, where other concepts of sustainable development, sustainable management,and sustainable consumption could be regarded as instruments towards achieving the sustainability goal (Voigt, 2005).